Psychogenic seizures: long‐term outcome in patients with and without epilepsy. (14th July 2015) - Sadan, O.; Neufeld, M. Y.; Parmet, Y.; Rozenberg, A.; Kipervasser, S.
Abstract : Objectives: Psychogenic non‐epileptic seizures (PNES) may resemble epileptic events. Epileptic and non‐epileptic seizures are not mutually exclusive phenomena and may coexist in the same patient. The aim of this study was to evaluate the long‐term outcome of psychogenic events in patients with PNES alone and those with both PNES and epilepsy (PNES + EPI) as diagnosed by video‐EEG (vEEG) monitoring. Materials and Methods: All adult admissions to the Tel‐Aviv Medical Center's vEEG unit between 2004 and 2009 were screened for the presence of PNES. We retrospectively retrieved data from their medical files and supplemented the follow‐up by a telephonic questionnaire. Results: Eligible patients ( n  = 51) were divided into those with PNES + EPI ( n  = 24) and those with PNES alone ( n  = 27). The follow‐up period was 4.8 ± 0.3 and 4.3 ± 0.3 years, respectively. Both groups had similar female predominance and similar age at admission to the vEEG unit. Time from PNES onset to hospitalization was longer in PNES patients compared to those with PNES + EPI. The majority of subjects in each group reported a history of at least one major stressful life event. Opisthotonus was significantly more frequently observed in PNES patients, and they had more events during vEEG hospitalization. Psychogenic events ceased during the follow‐up period in 22% of the PNES patients and in 58% of the PNES + EPI patients ( P  > 0.001). Conclusion: Our results indicate that following vEEG‐based diagnosis of PNES, the long‐term outcome of PNES cessation may be more favorable for patients with concomitant epilepsy than for patients without epilepsy.